Amiloride as an Alternate Adjuvant Antiproteinuric Agent in Fabry Disease: The Potential Roles of Plasmin and uPAR - H. Trimarchi; M. Forrester; F. Lombi; V. Pomeranz; M. S. Raña; A. Karl; J. Andrews (Case Reports in Nephrology)
Patients with Fabry disease present a higher risk of cardiovascular and kidney morbidity. We present a patient with a past history of biopsy-proven Fabry disease and stage 3 chronic kidney disease. Proteinuria partially dropped from 6.8 g/day to 2.1 g/day despite an aggressive regime which consisted of low-salt diet, agalsidase beta infusions, dual blockade of the renin-angiotensin system, and low-dose maintenance of steroids. As proteinuria is considered a risk marker of cardiovascular disease and of progression of kidney disease, we added amiloride 5 mg/day, a drug with proven effects in podocyte stabilization and proteinuria actions at the distal convoluted tubule. Proteinuria finally decreased to 0.8 g/day. This report highlights the relevance of intervening on proteinuria in a multitarget approach in order to reduce it as much as possible. Due to this pharmacological response, we suggest that although agalsidase beta specific treatment protects the endothelium, the podocyte, and the tubule in Fabry disease and secondary haemodynamic and immunologic pathways are treated with inhibition of the renin-angiotensin system and steroids, amiloride may act as a complementary tool in podocyte stabilization and in proteinuria effects at the distal tubule.